1986
DOI: 10.1007/bf01625188
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of synaptic ribbons in the developing organ of Corti

Abstract: Studies of synaptogenesis in the developing organ of Corti in the intact mouse and in culture indicate that the inner and outer hair cells contain three populations of synaptic ribbons, i.e. ribbons adjacent to nerve fibres, free intracellular ribbons and misplaced ribbons apposed to non-neuronal elements. Ribbons adjacent to nerve fibres can be further classified into: ribbons synaptically engaged, ribbons participating in formation of presynaptic complexes only and ribbons that are not engaged to the hair ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
107
4

Year Published

1990
1990
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(129 citation statements)
references
References 19 publications
18
107
4
Order By: Relevance
“…The presence of ribbon-associated and ribbon-free afferent synapses was also seen in 3D reconstructions from serial section TEM of mouse OHCs. These showed that half of all afferent contacts were ribbon-free, reminiscent of earlier reports of ribbon-less contacts in various species (Dunn and Morest 1975;Francis and Nadol 1993;Liberman et al 1990;Nadol 1983;Sobkowicz et al 1986). Pre-and postsynaptic immunolabeling in rat showed that only half of the postsynaptic densities in type II boutons were associated with ribbons in OHCs (Martinez-Monedero 2016).…”
Section: Discussionsupporting
confidence: 75%
“…The presence of ribbon-associated and ribbon-free afferent synapses was also seen in 3D reconstructions from serial section TEM of mouse OHCs. These showed that half of all afferent contacts were ribbon-free, reminiscent of earlier reports of ribbon-less contacts in various species (Dunn and Morest 1975;Francis and Nadol 1993;Liberman et al 1990;Nadol 1983;Sobkowicz et al 1986). Pre-and postsynaptic immunolabeling in rat showed that only half of the postsynaptic densities in type II boutons were associated with ribbons in OHCs (Martinez-Monedero 2016).…”
Section: Discussionsupporting
confidence: 75%
“…However, this study at least demonstrates that removal of afferent innervation at birth does not hinder further development of OHCs. A similar conclusion was also reached by Sobkowicz et al (1986), who demonstrated that removal of afferent innervation at birth did not hinder further morphological development of hair cells or cause any degeneration of the organ of Corti in tissue culture.…”
Section: Ontogeny Of Ohc Motility Does Not Require Neurotrophic Effecsupporting
confidence: 74%
“…A number of investigations were also targeted to the question of how the presence of neuronal elements or the pattern of innervation exert influence on the cytodifferentiation of sensory cells (Knowlton, 1967;Orr, 1968;Sher, 1971;Thornhill, 1972;Van de Water, 1976, 1986, 1988Van de Water et al, 1984Pirvola et al, 1991). No attempt has been made to test directly the hypothesis that efferent innervation regulates the maturation of OHCs.…”
Section: Ontogeny Of Ohc Motility Does Not Require Neurotrophic Effecmentioning
confidence: 99%
“…Second, weak CDI could help prolong Ca 2ϩ entry that would sustain activity-dependent transcription underlying outer hair cell development (Platzer et al, 2000;Brandt et al, 2003;Glueckert et al, 2003). During the development of hearing, cochlear hair cells undergo major changes in potassium (Kros et al, 1998;Marcotti et al, 2003) and calcium channel expression (Beutner and Moser, 2001;Michna et al, 2003), as well as dramatic rearrangement of efferent and afferent innervation (Liberman and Simmons, 1985;Sobkowicz et al, 1986Sobkowicz et al, , 2004Simmons and Liberman, 1988a,b;Simmons et al, 1992Simmons et al, , 1996Simmons, 1994Simmons, , 2002Fuchs et al, 2003;Bergeron et al, 2005). Hence, the early presence of Ca V 1.3 IQ⌬ channels, as well as the loss of OHCs shortly after the onset of hearing in Ca V 1.3 knock-out mice (Platzer et al, 2000), cohere with a contribution of these channels to activity-dependent gene expression underlying development.…”
Section: Discussionmentioning
confidence: 99%